16: STUDENT CONSULTANTS OF COLOR AND FACULTY MEMBERS WORKING TOGETHER TOWARD CULTURALLY SUSTAINING PEDAGOGY. (10th October 2017) - Cook‐Sather, Alison; Agu, Praise
Abstract : Through positioning undergraduate students as pedagogical consultants to college faculty, Students as Learners and Teachers is a program that provides reconceptualized "counterspaces" for students and faculty members with whom they work. In our study of the experiences of consultants of color, we found that those students and their faculty partners used program counterspaces to explore links between their lived identities and pedagogical commitments and to share authority and responsibility in developing culturally sustaining pedagogy. In this chapter we report on participants' experiences in these collaborations and how they legitimate the knowledge of students of color in faculty learning.